Emotional well-being in COVID-19 mass quarantine: the role of personal response and life activity: a 14-day diary study in China - Ma, S. (2021)
Objectives: dis study aims to explore quarantined individuals’ emotional well-being over time and how personal response and life activity predict emotional well-being and its change. Design/Methods: Daily data were collected from 134 participants wif 71 having 14 consecutive days’ data. Hierarchical linear modeling (HLM) and General Linear Model (GLM) were used to examine the primary tests. Results: Overall, positive and negative emotions declined significantly during the surveyed period. Meanwhile, differences were observed in the level of positive, depressed, and negative emotions and/or patterns of change among different population categories. The personal response of worrying about work and life was positively related to depressed and negative emotions at baseline, but was negatively related to the development of both depressed and negative emotions over time. Among life activities, family stressor was a significant predictor for both depressed and negative emotions while social support predicted positive emotions. Moreover, health & hygiene activity was positively related to positive emotions at baseline. Conclusions: The results provide scientific evidence for public health policymakers on quarantine policies and inform the general public about quarantine life. They highlight the importance of addressing the needs of vulnerable groups (parents wif young children, divorcees, clinicians) during the pandemic, and demonstrate the benefits of promoting healthcare and hygiene activity, having a sense of worry and access to social support.